CURRENT STATUS OF HIV/AIDS-SYPHILIS CO-INFECTIONS: A RETROSPECTIVE MULTICENTRE STUDY - Sargul, Figen; Sayan, Murat; Inan, Dilara; Deveci, Aydin; Ceran, Nurgul; Celen, Mustafa Kemal; Buyuktuna, Seyit Ali (Natl Inst Public Health, 2019)
Objective: Treponema pallidum and HIV are transmitted frequently through sexual contact, these agents with epidemiological similarities co-infect the same host. The current number of HIV-infected cases in Turkey is increasing. For this reason, we aimed to reveal the characteristics of syphilis in HIV/AIDS cases. Methods: A retrospective longitudinal cohort study was performed, patients were followed up at 24 clinics in 16 cities from all seven regions of Turkey between January 2010 to April 2018. We examined the socio-demographic characteristics, laboratory parameters and neurosyphilis association in HIV/AIDS-syphilis co-infected cases. Results: Among 3,641 patients with HIV-1 infection, 291 (8%) patients were diagnosed with syphilis co-infection. Most patients were older than 25 years (92%), 96% were males, 74% were working, 23% unemployed, and 3% were students. The three highest prevalence of syphilis were in Black Sea (10.3%), Mediterranean (8.4%) and Marmara Regions (7.4%). As for sexual orientation, 46% were heterosexuals, 42% men who have sex with men (MSM), and no data available for 12%. Patients with the number of CD4+<= 350 mm(3) reached 46%, 17% of the patients received antiretroviral therapy and neurosyphilis association reached 9%. Conclusion: Although HIV/AIDS-syphilis co-infection status appeared high in heterosexuals, MSM had a moderate level increase in cases. Our results suggested syphilis co-infection in HIV/AIDS cases should be integral part of monitoring in a national sexual transmitted diseases surveillance system. However, our data may provide base for HIV/syphilis prevention and treatment efforts in the future.
Keywords: syphilis; HIV; sexually transmitted diseases